Ameliorative Role of Silymarin in Methotrexate-Induced Pulmonary Damage: A Multi-Pathway Molecular Approach - Genc, Aydin; Sahin, Emre; Cankaya, Eren (Wiley, 2026)
Methotrexate (MTX) is a medication that is frequently prescribed for the treatment of both malignant disorders and inflammatory pathologies. However, its use is limited by dose-dependent pulmonary toxicity. The present study investigated the protective effects of silymarin (SLM) against MTX-induced lung injury by evaluating apoptosis, oxidative stress, autophagy, inflammation and histopathological changes in rats. Twenty-eight Wistar albino rats were assigned to the Control, SLM (50 mg/kg, p. o.), MTX (20 mg/kg, i. p.), and MTX + SLM groups. MTX treatment led to a significant elevation in malondialdehyde levels along with marked reductions in glutathione content and antioxidant enzyme activities, concomitant with decreased Nrf2 and HO-1 expression, indicating pronounced oxidative stress (p < 0.05). Additionally, MTX has been shown to raise Bax and Caspase-3 and diminish Bcl-2 while simultaneously inducing NF-kappa B, TNF-alpha, TLR-4, and HMGB1. This confirms the presence of increased inflammation and mitochondrial-dependent apoptosis (p < 0.05). Furthermore, MTX elevated the expression of LC3A, LC3B, and Beclin-1, suggesting an increase in autophagy (p < 0.05). SLM supplementation greatly improved antioxidant status, increased Nrf2/HO-1, decreased inflammatory signaling, modulated Caspase-3/Bax/Bcl-2 expression, and suppressed MTX-induced autophagy (p < 0.05). These biochemical findings were subsequently corroborated by histopathological analysis. In summary, the present study demonstrates that SLM offers a promising protective effect against MTX-induced pulmonary damage, operating through mechanisms involving antioxidant, anti-autophagic, anti-inflammatory and anti-apoptotic actions. These results underscore the potential of SLM as a complementary therapeutic agent in mitigating lung toxicity induced by chemotherapy agents.
Keywords: inflammation; lung injury; methotrexate; oxidative stress; silymarin